1982
DOI: 10.1002/jso.2930200103
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic regional perfusion with melphalan and a combination of melphalan and actinomycin D in the treatment of locally metastasized malignant melanomas of the extremities

Abstract: From September 1969 through 1979, 68 patients with already locally metastasized malignant melanomas of the extremities were treated by hyperthermic regional perfusion and local excision(s). Of these, 53 patients could be evaluated after a follow-up of at least 2 years: 31 had been perfused with melphalan and 22 with melphalan in combination with actinomycin D. Local recurrence rates were about the same in both groups: 32 versus 33%. The same applied to the symptom-free interval between perfusion and local recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Their work has prompted others to undertake similar studies. Rochlin and Smart [16], Krementz et al [10], Krementz and Campbell [11], Shingleton [21], Stehlin et al [3,22], McBride et al [7], Martijn et al [13][14][15], Schraffordt Koops et al [18--20], Johnsson et al [9], Illig and Aigner [8], Lejeune et al [12], Sugarbaker and McBride [23], Vaglini et al [25], Tonak et al [24], and Aigner et al [6] have achieved reasonable long-term survivals in selected patients with recurrent limb melanoma treated by surgical excision and adjuvant perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their work has prompted others to undertake similar studies. Rochlin and Smart [16], Krementz et al [10], Krementz and Campbell [11], Shingleton [21], Stehlin et al [3,22], McBride et al [7], Martijn et al [13][14][15], Schraffordt Koops et al [18--20], Johnsson et al [9], Illig and Aigner [8], Lejeune et al [12], Sugarbaker and McBride [23], Vaglini et al [25], Tonak et al [24], and Aigner et al [6] have achieved reasonable long-term survivals in selected patients with recurrent limb melanoma treated by surgical excision and adjuvant perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…We have published 2 articles about patients treated by regional perfusion who had locally metastasized malignant melanomas of the extremities [14,15]. Only patients with local recurrence, satellitosis, or intransit metastases with or without lymph node metastases were analyzed in these studies.…”
Section: Perfusion In Patients With Local Recurrence Of Lntransit Met...mentioning
confidence: 99%
See 1 more Smart Citation
“…Actinomycin D is an anticancer antibiotic that has been used in patients with osteogenic sarcoma in combination with bleomycin and cyclophosphamide but this treatment is associated with severe nausea and anorexia (69). Martijn et al showed that melphalan-based ILP with actinomycin D in patients with IT-mets offer no improved response rates compared to melphalan alone (70). However, actinomycin D increase the TNF sensitivity of tumor cells in vitro (71) and local administration of TNF in combination with actinomycin D in mice delays the growth of several tumors (72,73).…”
Section: The Isolated Limb Perfusionmentioning
confidence: 99%
“…A number of agents have been administered via ILP including cisplatin [39,[56][57][58][59][60], cisplatin and etoposide [61], melphalan and actinomycin D [62], DTIC [63,64], or IL-2 and LAK cells [64,65]. Despite the substantial clinical experience with other agents it does not appear that any have superior efficacy or less toxicity than melphalan alone [66].…”
Section: Isolated Limb Perfusion With Other Agentsmentioning
confidence: 99%